The Conservation Management Model For Mangrove Forest Management And Ecotourism On Wangi-Wangi Island, Wakatobi, Indonesia: A Moderated-Mediation Approach Involving Community Empowerment And Institutional-Motivational Barriers - Sahari, Sariamin; RUMPA, ARHAM; FERLIN, AKHMATUL; ADMAJA, ALFI KUSUMA; ASUHADI, SUNARWAN; Musrianton, Muhammad; ISMAN, KHAIRUDIN; MANSYUR, LA ODE; NORMAYASARI, NORMAYASARI; Ikhsan, Nur; NASRUN, NASRUN; HARUDIN, HARUDIN; JABBAR, MEUTHIA AULA (Politeknik Kelautan dan Perikanan Karawang, 2026)
The management of mangrove conservation and ecotourism on Wangi-Wangi Island in Wakatobi employs a Moderated-Mediation approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to understand the complex mechanisms between conservation and ecotourism efforts, community empowerment, and the sustainability of ecotourism. This study also examines the moderating role of institutional barriers and motivation. Mangrove ecosystems are threatened by anthropogenic factors and the lack of management institutions, particularly in Wakatobi, which possesses the local wisdom of its indigenous communities but faces challenges related to infrastructure and community participation, often limited to a tokenistic level. The research method involved a survey with a 5-point Likert questionnaire administered to 100 respondents from various stakeholders across four coastal villages. Data analysis was performed using SEM-PLS 4.0 software to test for validity, reliability, and model hypotheses, alongside descriptive qualitative data interpretation. Results indicate that although the direct impact of conservation and ecotourism on sustainability is not significant, community empowerment significantly mediates this relationship with an indirect effect of 0.587. Furthermore, institutional barriers and motivation were not found to be significant moderators, even though they remain contemporary issues. Thus, the sustainability of mangrove ecotourism in Wangi-Wangi largely depends on effective community empowerment as a key mediator, rather than direct conservation and ecotourism efforts. Consequently, policy recommendations should focus on strengthening community empowerment, particularly through political and participatory dimensions, enhancing citizen oversight, and improving structural governance, including infrastructure and regulations, to address existing barriers